Error analysis of prospective mathematics teachers in solving of applying radian measurement problem in trigonometry courses - Setiawan, Yayan Eryk; Surahmat, Surahmat (Universitas Islam Raden Intan Lampung, INDONESIA, 2021)
This research aims to describe the mistakes of the prospective teachers in solving the application of radian measurement problems and their causes. This type of research is qualitative descriptive research with a case study approach. The types of data collection in this research consisted of the results of the subject's work and transcripts of interviews with research subjects. By following the type of data, this research instrument consists of one question about the problem of applying radian measurement and interview guidelines developed by the researchers. Data analysis of the subject's work is carried out by classifying the types of errors to know the types of errors that arise in solving the problem of applying the radian measurements. While the transcript analysis of the interview results was carried out by coding the words to determine the factors causing the errors that appeared. The results of the research indicate that the error in solving the problem of applying the radian measurement are misconceptions and factual errors. This misconception is generally caused by intuitive thinking, while this factual error is generally caused by not paying careful attention to the information in the question. The solution to these errors is to analyze the elements of the circle that are interconnected in solving the problem of applying the radian measurements and to be careful in writing the information that is known in the question.